Optimal Catheter Ablation Strategy for Patients with Persistent Atrial Fibrillation and Heart Failure: A Retrospective Study - Cheng-ming Ma; Ye-jian He; Wen-wen Li; Hua-min Tang; Shi-yu Dai; Xiao-meng Yin; Xian-jie Xiao; Yun-long Xia; Lian-jun Gao; Yuan-jun Sun; Zhong-zhen Wang; Rong-feng Zhang (Cardiology Research and Practice)
The optimal catheter ablation (CA) strategy for patients with persistent atrial fibrillation (PeAF) and heart failure (HF) remains uncertain. Between 2016 and 2020, 118 consecutive patients with PeAF and HF who underwent the CA procedure in two centers were retrospectively evaluated and divided into the pulmonary vein isolation (PVI)-only and PVI + additional ablation groups. Transthoracic echocardiography (TTE) was performed at baseline, one month, and 12 months after the CA procedure. The HF symptoms and left ventricular ejection fraction (LVEF) improvements were analyzed. Fifty-six patients underwent PVI only, and 62 patients received PVI with additional ablation. Compared with the baseline, a significant improvement in the LVEF and left atrial diameter postablation was observed in all patients. No significant HF improvement was detected in the PVI + additional ablation group than in the PVI-only group (74.2% vs. 71.4%, P=0.736), but the procedure and ablation time were significantly longer (137.4 ± 7.5 vs. 123.1 ± 11.5 min, P=0.001). There was no significant difference in the change in TTE parameters and the number of rehospitalizations. For patients with PeAF and HF, CA appears to improve left ventricular function. Additional ablation does not improve outcomes and has a significantly longer procedure time. Trial registration number is as follows: ChiCTR2100053745 (Chinese Clinical Trial Registry; https://www.chictr.org.cn/index.aspx).